Alterações cinemáticas e características de carga de treinamento em corredores e corredoras com dor patelofemoral - Luz, Bruna Calazans (2021)
Recreational running is one of the most practiced physical activities in the world. Although this activity offers numerous physiological and psychological health benefits, running has a high incidence of injuries. Patellofemoral pain (PFP) is one of the running-related injuries that most affect runners, and females are twice as likely to develop it. Although the etiology of PFP is not yet fully understood, several etiological factors are proposed for this musculoskeletal disorder. Among them, intrinsic factors, such as altered kinematics of the lower limbs, and extrinsic factors, such as training load characteristics, have been reported as possible causes for the development of PFP. However, the relationship of these factors with the intensity of pain and physical function of female and male runners with PFP, in addition to the possible influence of sex on the kinematics of these runners, has not yet been reported in the literature. Therefore, the objectives of the thesis were: 1- to verify whether there is an association between hip and knee kinematics and running training load with pain intensity and functional status in males and females with PFP and 2- to investigate whether changes in hip and knee kinematics during running in runners with PFP are sex-specific. Runners of both sexes, with and without PFP and aged between 18 and 35 years, were evaluated. The kinematic evaluation was performed on a treadmill during the stance phase using a 3D system and the variables of interest were: hip adduction, hip internal rotation and knee abduction. To assess pain and physical function, the visual analogue scale and the Anterior Knee Pain Scale (AKPS) questionnaire validated for the Portuguese language were used. Results indicated that longer weekly distance was associated with greater pain intensity in females with PFP, but there was no association between lower limb kinematics or running pace with pain intensity and physical function in both males and females with PFP. Furthermore, although females had greater hip adduction than males, regardless of the presence of PFP, there was no difference between females with and without PFP for this variable. Alterations in other kinematic variables evaluated (knee abduction and hip internal rotation) were also not sex-specific in runners with PFP. We conclude that hip and knee altered kinematics in runners with PFP are not sex-specific; in addition, clinicians should not only assess and treat the biomechanical factors of runners with PFP, but also be aware of training loads, especially with increasing weekly distance.